Vers l’établissement d’une « nationalité noire » ? Le rêve haïtien de James Theodore Holly - Claire Bourhis-Mariotti (IdeAs)
The thirty years preceding the Civil War saw the emergence of a radical and immediatist abolitionist movement, particularly among Blacks who, for the most part, adhered to the ‘stay and fight’ ideology. Most African-American leaders were then firmly opposed to emigration and denounced the American Colonization Society and its African projects. Yet, at the very same time, a number of black activists did advocate relocation beyond the borders of the United States, but struggled to find a consensus concerning the place where they should settle. At the beginning of the 1850s, James Theodore Holly, a free Black, started promoting the virtues of emigration to Haiti more specifically. With the help of a white abolitionist, James Redpath, commissioned by the Haitian government itself, Holly encouraged his peers to move to the Black Republic, which he considered as the best place to (re)construct the black community. Thus, this article will examine in what conditions thousands of African-Americans decided to leave their homeland and relocate in Haiti. This Haitian experience, a subject that has been marginalized in the historiography of slavery, abolition and colonialism, was part of a larger and more complex process, namely the birth of black nationalism. The author therefore intends to contribute to a reconsideration of black efforts to encourage emigration, in order to show the real diversity in black abolitionist and nationalist thought on the eve of the Civil War.